2016
DOI: 10.1111/bjc.12122
|View full text |Cite
|
Sign up to set email alerts
|

Service user satisfaction with cognitive behavioural therapy for psychosis: Associations with therapy outcomes and perceptions of the therapist

Abstract: Therapy expectations represent a neglected area of research and may have implications for levels of satisfaction with therapy and perceived benefit. The findings reinforce the importance of cognitive behavioural therapy for psychosis (CBTp) therapists demonstrating that they are supportive, competent, and trustworthy. The findings suggest that positive experiences of therapy do not require changes in psychosis symptoms and are instead related to changes in quality of life. Depressive symptoms at the start of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…[ 36 ] Ninety-six percent of beneficiaries reported satisfaction with CBT. [ 37 ] Higher levels of overall satisfaction and perceived benefit from CBT can be associated with positive therapy expectations, positive ratings of therapist's personal characteristics, competence and trustworthiness, lower pre-therapy depression, and improvements in quality of life. [ 37 ] Participants reported higher life satisfaction at the end of a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Ninety-six percent of beneficiaries reported satisfaction with CBT. [ 37 ] Higher levels of overall satisfaction and perceived benefit from CBT can be associated with positive therapy expectations, positive ratings of therapist's personal characteristics, competence and trustworthiness, lower pre-therapy depression, and improvements in quality of life. [ 37 ] Participants reported higher life satisfaction at the end of a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Higher levels of overall satisfaction and perceived benefit from CBT can be associated with positive therapy expectations, positive ratings of therapist's personal characteristics, competence and trustworthiness, lower pre-therapy depression, and improvements in quality of life. [ 37 ] Participants reported higher life satisfaction at the end of a previous study. [ 38 ] Hofmann et al [ 39 ] found that CBT for anxiety disorders is moderately effective for improving quality of life, especially in physical and psychological domains.…”
Section: Discussionmentioning
confidence: 99%
“…An amended service-specific 22-item version of the STQ (60) was administered at the end of therapy to obtain further data regarding the acceptability of the intervention. The STQ is an adaptation of Beck et al’s (59) Patient’s Report of Therapy Session and was first used to assess satisfaction with CBTp by Kuipers et al (61).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, a recent narrative review of 22 qualitative studies revealed that persons with insomnia expressed a sense of frustration related to healthcare providers' misunderstanding of their problem and prescription of treatments (usually medication and SEH) that did not correspond to their perspective and experience of insomnia (AraĂșjo, Jarrin, Leanza, ValliĂšres, & Morin, 2016). Accordingly, the prescribed treatments might not have met our participants' expectations, which could have resulted in treatment dissatisfaction and only a minimal improvement in outcomes (Lawlor et al, 2017). Persons with chronic insomnia are also likely to seek alternative treatments from other sources, including relatives, friends and the Internet.…”
Section: Discussionmentioning
confidence: 93%